Dental considerations in the management of children suffering from sickle cell disease: A case report - Ramakrishna Y (Wolters Kluwer Medknow Publications, 2007)
Sickle cell disease (SCD) is a genetically derived disorder characterized by the presence of an abnormal hemoglobin molecule, designated as hemoglobin S (HbS). It is one of the most common genetic disorder worldwide, with an estimated 70 million people carrying the sickle gene. This article describes the dental considerations in managing a 6-year-old child suffering from SCD (SS type).